Evaluating Alumni Communication and Curriculum Relevance: A Tracer Study of Tadris Mathematics Department at IAIN Syekh Nurjati Cirebon - Kusmanto, Hadi (Ilmu Inovasi Nusantara, 2024)
Nowadays, tracer studies are widely applied to trace events or facts. In this research, tracer study was used to find out and improve the quality and communication of alumni of the Tadris Mathematics Department of IAIN Syekh Nurjati Cirebon. Improved communication is very useful for the smooth flow of information from alumni to other parties in a reciprocal manner. The objectives of this research are: 1) Explore information about the gap between the education provided and the world of work, 2) Find out the relevance of curriculum implementation, 3) Evaluate the relationship between the curriculum and studies in the department as scientific development. The methodology used is tracer study, with a sampling technique using snowball sampling. Based on the research results, the following results were obtained: 1) There is a gap between the education provided and the world of work. This is proven by the lack of skills courses and practical courses. Of the 29 graduate skills courses, there are only 5 courses that are skills in nature and 5 that contain practicum. 2) There are 53 students who have obtained jobs and which match their competencies. There were 23 students who got jobs and those who were not suitable. Meanwhile, 10 people did not fill out this questionnaire. This means that alumni students majoring in mathematics have competencies appropriate to their type of work. 3) The curriculum developed in the department is still not well integrated. This occurs due to a lack of attention from lecturers to aspects of the curriculum